Pengetahuan dan sikap orang tua terhadap status imunisasi anak di Bantul - Titik Mariati; Djauhar Ismail; Mohammad Hakimi (Berita Kedokteran Masyarakat (BKM), 2017)
Knowledge and attitudes of parents about child immunization status in BantulPurposeThe purpose of this paper was to determine the relationship of knowledge, and parental attitudes with the status of child immunization in the working area of Puskesmas Banguntapan II Bantul Yogyakarta.MethodsA cross-sectional study was conducted involving the mothers of 0-12 months old children in the working area of Banguntapan II Bantul Yogyakarta Primary Health Care. Simple random sampling was used.ResultsThe results showed that there was a significant attitude relationship with the immunization status of their children with high category as much as 86.9%. These results showed that as much as 86.9% immunization status of children are not complete. The OR value of knowledge was 0.7 with a CI value of 0.15 to 4.04. This model shows that the knowledge of respondents with parental attitudes is meaningful both statistically and practically.ConclusionThis study contributes to the knowledge that there is a significant relationship between parental attitudes with child immunization status in the working area of Banguntapan II Bantul Yogyakarta Primary Health Care.